Factors Affecting To Accounting Fraud Tendencies: Study Of South Tapanuli District North Sumatera Province - Amelia Hasibuan; Arfan Ikhsan; Esa Setiana (Asosiasi Dosen Akuntansi Indonesia, 2020)
The aims of this research are to know the influence of: 1) Effect of Internal Control Effectiveness on Tendency Accounting Fraud in Local Government Institution of Tapanuli Selatan. (2) Effect of Composition Satisfaction on Tendency of Accounting Fraud in Local Government Institution of Tapanuli Selatan (3) Effect of Compliance to Accounting Rules on Tendency of Accounting Fraud Local Government Institution of Tapanuli Selatan. (4) Influence of Internal Control Effectiveness, Composition Satisfaction, and Compliance to Accounting Rules on Tendency of Accounting Fraud in Local Government Institution of Tapanuli Selatan. The method of collecting data used in this research is questionnaire. The population in this research consited of 90 employees of in Local Government Institution) of Tapanuli Selatan who were still actively working. The questionnaire had been tested validity and reliability. Test requirements analysis included tests for normality, multi-co-linearity test, heteroscedasticity test, linearity test. Analysis of the data used to test the hypothesis was to use the technique of multiple regression analysis. The results of this study are: (1) internal control compliance negatife and significant effect on accounting fraud tendency (2) Satisfaction Compensation positive and not significant effect on accounting fraud tendency (3) Compliance to Accounting Rules significant negative effect on Accounting Fraud Tendency. (4) Simultaneously Internal Control Compliance, Satisfaction Compensation and Compliance with Accounting Rules.